Chitin and Chitosan Physicochemical Properties and Industrial Applications - Berrada, Mohammed (IntechOpen, 2021)
Chitin and Chitosan - Physicochemical Properties and Industrial Applications provides an overview of the extraction, modification, characterization, and application of chitin and chitosan derivatives from crustacean byproducts and their physicochemical properties. It presents and explains important studies and develops new and innovative methods of biological and physicochemical analysis in the fields of organic and mineral environmental pollution, corrosion inhibitors, drug delivery systems, superabsorbent materials, nanotechnology, textiles, biotechnology, and biomedical sciences.